PELATIHAN MANAJEMEN INDUSTRI USAHA PENGOLAHAN PRODUKSI ABON IKAN TUNA DI DESA LAPANG BARAT KABUPATEN BIREUEN - Defi Irwansyah; Nurhafni Nurhafni; Ilham Saputra; Rizki Munandar (LPPM Universitas Al Muslim, 2022)
The solution offered to partners' problems in managing tuna production is an effort to increase partners' income so that they can produce better tuna in quality and quantity. Second, with modern technology in the production of shredded tuna by providing better packaging so that consumers are more interested, the abon processing business can create independent economic income. Problems faced by partners include the lack of processing facilities that meet industrial standards, the need for good business management, and ineffective marketing by partners. The results of this service provide solutions for standard ergonomics that are used, and the processing site must be really comfortable to use and sterile as well as good and sterile tuna processing methods, provide material on business management, including management procedures starting from the process of providing raw materials, processing production and financial management by recording cash inflows and outflows. Furthermore, there is marketing in the sale of shredded tuna by using marketing strategies such as WhatsApp and the web to reach partners based on social media. The results of this service are: the creation of an ideal shredded tuna fish production business; second management (governance) of shredded tuna production, processed fish that meets standards, modern marketing processes, and proper targeted shredded tuna processing, as well as increasing partner income.